2016
DOI: 10.3390/ijms17091455
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Ghrelin Accelerates the Healing of Acetic Acid-Induced Colitis in Rats

Abstract: Previous studies have shown that ghrelin reduces colonic inflammation induced by trinitrobenzene sulfonic acid and dextran sodium sulfate. In the present study we determined the effect of treatment with ghrelin on the course of acetic acid-induced colitis in rats. Rectal administration of 3% acetic acid solution led to induction of colitis in all animals. Damage of the colonic wall was accompanied by an increase in mucosal concentration of pro-inflammatory interleukin-1β (IL-1β) and tumor necrosis factor-α (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 71 publications
1
38
0
Order By: Relevance
“…Pretreatment with this polypeptide inhibits the development of different experimental models of gastric lesions [ 11 , 12 , 13 ], as well as exhibits therapeutic effect in the course of oral [ 14 ], gastric [ 15 , 16 ] and duodenal [ 15 , 17 ] ulcers. In addition, most experimental studies on the role of ghrelin in colitis indicates that administration of this peptide exhibits protective and therapeutic effect in the large bowel [ 18 , 19 , 20 , 21 , 22 , 23 ]. Protective and therapeutic effect of ghrelin was also found in the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with this polypeptide inhibits the development of different experimental models of gastric lesions [ 11 , 12 , 13 ], as well as exhibits therapeutic effect in the course of oral [ 14 ], gastric [ 15 , 16 ] and duodenal [ 15 , 17 ] ulcers. In addition, most experimental studies on the role of ghrelin in colitis indicates that administration of this peptide exhibits protective and therapeutic effect in the large bowel [ 18 , 19 , 20 , 21 , 22 , 23 ]. Protective and therapeutic effect of ghrelin was also found in the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…However, free radicals, such as reactive oxygen and nitrogen species, can damage body cells, leading to the destruction of proteins, DNA and lipids. Eventually, such destruction causes colonic tissue damage and mucosal dysfunction, which play a significant role in the pathogenesis of IBD [ 30 ]. The level of MPO activity adequately reflects the degree of tissue infiltration by neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of IGF-1 to promote this regeneration of tissue is associated with a reduction in pro-inflammatory cytokines and a corresponding stimulation of anti-inflammatory cytokines [ 31 ]. Additionally, ghrelin, a growth hormone secretagogue produced mainly in the stomach, was shown to exhibit protective and regenerative effects in various tissues via an increase in the release of endogenous IGF-1 and growth hormone [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. A recent study also found ghrelin promoted an increased expression of homeobox protein B4 in rat bone marrow stromal cells, which is a transcription factor involved in stem cells’ survival and regeneration [ 42 ].…”
Section: Introductionmentioning
confidence: 99%